A Novel Treatment Using an Intraventricular Stent Graft for Postinfarction Ventricular Septal Rupture in a Porcine Model. Issue 1 (January 2017) - Nishida, Yuji; Tomita, Shigeyuki; Kiuchi, Ryuta; Ohtake, Hiroshi; Watanabe, Go
Abstract : Objective: Ventricular septal rupture (VSR) is a severe complication of acute myocardial infarction, and the conventional technique for repair is associated with high operative mortality. A novel intraventricular stent graft (IVSG) device was tested as a less invasive treatment for VSR; it does not require cardiopulmonary bypass, cardiac arrest, or left ventricular incision. Its effectiveness was assessed using animal experiments. Methods: Six pigs were placed on cardiopulmonary bypass. The VSR model was created by making a hole in the interventricular septum via the right ventricle. Animals were weaned off the bypass. The sheath encasing the device was advanced over the guidewire, and the IVSG was placed in the left ventricle. Before and after rupture creation and after device deployment, left ventriculography was performed, hemodynamic data were collected, and Qp/Qs values were measured. Results: All procedures were completed safely. The left-to-right shunt seen after rupture creation disappeared after device deployment. The pulmonary-to-systemic blood flow ratio after rupture was 3.35 ± 1.00, decreasing significantly to 1.09 ± 0.10 after device deployment ( P = 0.007). Hemodynamic instability after rupture creation improved dramatically after deployment. Conclusions: The use of our new IVSG in this VSR animal experiment model significantly decreased the left-to-right shunt. The new device was able to control the acute heart failure associated with VSR with a minimally invasive procedure during the hyperacute phase of heart failure. Potential improvements in VSR treatment outcomes are expected with its clinical application.